Corneoscleral patch graft combined with vitrectomy and intravitreal antibiotics for the management ofMorganella morganiiendophthalmitis. Issue 1 (January 2016) - Kelkar, Aditya S.; Lisa, Mona; Mulay, Aishwarya; Datar, Sameer
Abstract : N/A: We report a case of acute fulminant Morganella morganii endophthalmitis secondary to wound‐site infection reported on the sixth postoperative day after complicated cataract surgery in an elderly diabetic man. The case demonstrates effective management of this rare entity with a corneoscleral patch graft, vitrectomy, and intravitreal antibiotics. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.